Time to tax for inclusive growth (UN ECLAC, 2016)
Aims to contribute to efforts to combat inequality in Latin America by analysing the fiscal challenges involved and proposing policy guidelines. Posits that tackling inequality must be part of a new social compact to improve the state of the world, and building a fairer tax system must be part of any plan to tackle inequality and boost inclusive growth.
Keywords: TAX COLLECTION